The Phenomenal Concept Strategy and a Master Argument (KEMANUSIAAN The Asian Journal of Humanities, 2015)
The phenomenal concept strategy (PCS) is widely regarded as the most promising physicalist defence against the so-called epistemic arguments—the anti-physicalist arguments that establish an ontological gap between physical and phenomenal facts on the basis of the occurrence of epistemic gaps in our descriptions of these facts. The PCS tries to undercut the force of the epistemic arguments by attributing the occurrence of the epistemic gaps to the special character of phenomenal concepts—the concepts by means of which we think about our phenomenal experiences. In this essay, the author examines David Chalmers' master argument against the PCS and the objections raised against this argument by Peter Carruthers, Bénédicte Veillet and Katalin Balog in defending the PCS. While the author finds these objections to be successful defences of the PCS, the author shares Balog's belief that in this regard, the debate between the physicalists and anti-physicalists is a stalemate.